The independent and joint role of socioeconomic status and family relationships on mortality risk in China: cultural differences and health inequalities in the context of intergenerational cohabitation - Zhixi Zhu; Yiying Wang; Xin Wang; Fuyan Zhang; Lisha Yu; Tao Liu (Archives of Public Health)
Abstract Background Socioeconomic status (SES) and family relationships are critical social determinants of health disparities. The mechanisms underlying their interactions remain insufficiently understood in Asian cultures with prevalent intergenerational cohabitation. This study investigates the independent and combined effects of SES and family relationships on all-cause mortality in China. Methods A baseline survey was conducted in 2010 involving 9280 adult permanent residents from 12 counties (districts) in Guizhou Province, using stratified cluster random sampling. Two follow-ups (2016–2020, 2023) were conducted. SES was assessed using a composite score comprising household income, education, and occupation, while family relationships were classified as either "good" or "mediocre." The Cox proportional hazards model was employed to evaluate the independent and combined effects of SES and family relationships on all-cause mortality. Results Among 5949 participants were included, and the cumulative mortality rate was 6.4% over a median follow-up of 12 years. With a decrease in mortality risk as SES increased (P < 0.001). Compared with SES ≤ 6, mortality risk with SES scores of 7, 8, and ≥ 9 decreased by 36.9% (HR = 0.631, 95% CI = 0.473–0.842), 36.6% (HR = 0.644, 95% CI = 0.469–0.886), and 73% (HR = 0.270, 95% CI = 0.183–0.397), respectively. The independent effect of family relationship on the risk of death was not statistically significant (HR = 0.847, 95% CI = 0.0.670- 1.070). The joint analysis showed the compensatory effect was significant when SES exceeded a threshold (SES ≥ 9), alleviating the mortality risk associated with family relationships (HR = 0.2197, 95% CI = 0.073–0.652). Conclusion Findings demonstrate SES independently reduces mortality in Chinese populations, while the effect of family relationships is modulated by cultural background. The resource substitution hypothesis is valid at specific SES thresholds. Intervention efforts should prioritize the vulnerable group characterized by "low SES and weak family support".